Acculturation, adaptation, and loneliness among Cape Verdean immigrants. (March 2022) - Neto, Joana; Quintana-Orts, Cirenia; Neto, Félix
Abstract: Loneliness is a major public health concern, yet little is known in migrants. Therefore, understanding the risk factors for loneliness is relevant. The current study explores acculturation and sociocultural adaptation factors predicting loneliness regarding immigration. While little previous research has examined sociocultural adaptation as a mediator intervening between other predictors and psychological adaptation, this study tested the mediating role of sociocultural adaptation between perceived discrimination and loneliness. Cross-sectional data on 418 Cape Verdean immigrants (47.4% women) with an average age of 35 years were analyzed. The average length of living in Portugal was 18 years. Participants completed scales to evaluate acculturation strategies, ethnic identity, perceived discrimination, sociocultural adaptation, and a short form of the Revised UCLA Loneliness Scale (ULS-6). As expected, the results showed that greater levels of integration, greater ethnic identity, and lower perceived discrimination were related to lower levels of loneliness. Furthermore, our findings suggest that sociocultural adaptation indeed mediates the relationship between perceived discrimination and loneliness. Despite low levels of perceived discrimination experienced by Cape Verdean immigrants in Portugal, this antecedent plays an essential role in their experience of loneliness. The findings are discussed in terms of the conceptional context.